2017
DOI: 10.1016/j.yclnex.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight exposure vs. vitamin D supplementation on bone homeostasis of vitamin D deficient rats

Abstract: This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Clinical Nutrition Experimental 11 (2017) 1e9separation in the bone sections among vitamin D deficient rats, after sunlight exposure, were better. Conclusions: Sunlight-exposure have a more positive effect on bone structure and homeostasis than vitamin D supplementation and control. This effect was more with vitamin D deficient than vitamin D sufficient rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…This finding is consistent with previous studies exploring the links of vitamin D obtained via dietary intake or supplementation, serum 25(OH)D, and sunlight exposure with BMD, osteoporosis, or fractures [20,21,23,33]. One experimental study using rats reported that PTH was significantly reduced in the sun-exposed vitamin D-deficient group (67.69 ± 13.18 pg/ml) compared to the levels in the vitamin D-supplemented rats (78.93 ± 8.31 pg/ml) and vitamin D-deficient rats (86.05 ± 9.67 pg/ml) [22]. Regarding sunlight exposure in humans, one study demonstrated that high BG grade as a biomarker of lifetime UV radiation had beneficial associations with reduced fracture prevalence in females (fewer major fractures in women with higher BG grade than lower BG grade, relative risk (RR) = 0.75, 95% CI = 0.60-0.97) [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous studies exploring the links of vitamin D obtained via dietary intake or supplementation, serum 25(OH)D, and sunlight exposure with BMD, osteoporosis, or fractures [20,21,23,33]. One experimental study using rats reported that PTH was significantly reduced in the sun-exposed vitamin D-deficient group (67.69 ± 13.18 pg/ml) compared to the levels in the vitamin D-supplemented rats (78.93 ± 8.31 pg/ml) and vitamin D-deficient rats (86.05 ± 9.67 pg/ml) [22]. Regarding sunlight exposure in humans, one study demonstrated that high BG grade as a biomarker of lifetime UV radiation had beneficial associations with reduced fracture prevalence in females (fewer major fractures in women with higher BG grade than lower BG grade, relative risk (RR) = 0.75, 95% CI = 0.60-0.97) [23].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an experimental study demonstrated that sunlight exposure is more effective for improving bone structure than vitamin D supplementation in rats [22]. One study confirmed that fracture prevalence was inversely associated with lifetime ultraviolet (UV) radiation exposure according to the Beagley-Gibson (BG) grade in women [23].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D supplementation for children at risk is another option for consideration, though supplementation appears to be less effective than the effect of sunlight on the skin. A recent study demonstrated that vitamin D obtained from exposure to sunlight had a more positive effect than a vitamin D supplement on bone structure and certain hormones and minerals in vitamin D deficient rats, who presented with improved trabecular thickness, number and spacing after 10 days of sun exposure [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The source of vitamin D in mice is the same as in humans. Despite being covered by fur, rodents produce vitamin D from 7-dehydrocholesterol after exposure to sun [19], but due to their nocturnal life, mice have less opportunities than humans to expose themselves to sun. In addition, both species can absorb vitamin D from the diet and humans also use supplements [20].…”
Section: Vitamin D System In Humans and Micementioning
confidence: 99%